Perubahan Jaringan Hati Ikan Pari Kembang ( DASYATISKUHLI) Akibat Merkuri (HG) - Tresnati, Joeharnani; Trijuno, Dody Dharmawan; Djawad, Iqbal (Torani Journal of Fisheries and Marine Science, 2014)
Blue Spotted Ray (Dasyatis kuhlii) as the demersal organisms has a lot of accumulation of pollutants in the water that settles to the bottom. This study was conducted to look at the liver tissue alteration of Blue Spotted Ray caused by contamination of mercury (Hg). Performed on 5 tanks. Tank A as a control, tank B with concentration 0.025  ppm,  tank  C  with  concentration  of  0.05  ppm,  tank  D  with concentration  0.1  ppm  and  tanks  E  with concentration  0.2  ppm.  The  result  is  alteration  on  the  liver  tissue  in  the  form  of  atrophy,  cloudy  swelling, vacuolization degeneration and even necrosis or death of liver tissue already. The alteration can reduce and eveneliminate the function of the liver as a toxin absorbent and can lead to death.